2017
DOI: 10.21053/ceo.2015.01655
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Extrathyroidal Extension in Patients With Papillary Thyroid Microcarcinoma According to a BRAF Mutation

Abstract: ObjectivesThe aim of this study was to evaluate the association between preoperative parameters and extrathyroidal extension (ETE) of papillary thyroid microcarcinoma (PTMC) according to the BRAF mutation and to evaluate the preoperative predictability of ETE.MethodsWe analyzed the medical records of 332 patients with PTMC (140 in the BRAF– group and 192 in the BRAF+ group). The presence of ETE was subjected to a correlation analysis with age, sex, tumor size, clinical nodal status, and ultrasonography (US) fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In addition, BRAF mutational status has been correlated with recurrence of PTMCs, suggesting its importance in stratifying patients for surgical management 28 , 29 . On the other hand, several papers concluded that BRAF positivity is not significantly associated with most clinicopathologic features redolent of aggressiveness, including tumor multicentricity, lymphovascular invasion, extranodal extension, central neck involvement, advanced stage (stage III or IV), and distant metastasis 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BRAF mutational status has been correlated with recurrence of PTMCs, suggesting its importance in stratifying patients for surgical management 28 , 29 . On the other hand, several papers concluded that BRAF positivity is not significantly associated with most clinicopathologic features redolent of aggressiveness, including tumor multicentricity, lymphovascular invasion, extranodal extension, central neck involvement, advanced stage (stage III or IV), and distant metastasis 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…p values were calculated using the Wilcoxon rank sum test. *p < 0.05, **p < 0.01, and ***p < 0.001. studies, Chakraborty et al (2012) and Lee et al (2017) found that B-Raf proto-oncogene mutation status was significantly related to extrathyroidal invasion and lymph node metastasis. However, no studies identifying biomarkers of ETE in PTC have been reported.…”
Section: Discussionmentioning
confidence: 98%
“…It has relatively good prognosis and a low mortality rate (Xia et al, 2018). However, its prognosis is associated with several clinicopathological factors, including age, tumor size, distant metastasis, and the development of extrathyroidal extension (ETE; Hay et al, 1993;So et al, 2015;Lee et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Due to time costs, labor costs, and other expense issues, doctors and patients in China may be more inclined to choose surgery. Another important reason is more than 30% cervical lymph node metastasis in CN0 PTC and extrathyroidal extension [25,26]. With the application of ACR-TIRADS and ATA guidelines in recent years, this situation has been improving [27].…”
Section: Discussionmentioning
confidence: 99%